Novel DLX3 variants in amelogenesis imperfecta with attenuated tricho‐dento‐osseous syndrome. (9th September 2018) - Whitehouse, Laura L. E.; Smith, Claire E. L.; Poulter, James A.; Brown, Catriona J.; Patel, Anesha; Lamb, Teresa; Brown, Lucy R.; O'Sullivan, Elizabeth A.; Mitchell, Rowena E.; Berry, Ian R.; Charlton, Ruth; Inglehearn, Chris F.; et al.
Abstract: Objectives: Variants in DLX3 cause tricho‐dento‐osseous syndrome (TDO, MIM #190320), a systemic condition with hair, nail and bony changes, taurodontism and amelogenesis imperfecta (AI), inherited in an autosomal dominant fashion. Different variants found within this gene are associated with different phenotypic presentations. To date, six different DLX3 variants have been reported in TDO. The aim of this paper was to explore and discuss three recently uncovered new variants in DLX3 . Subjects and Methods: Whole‐exome sequencing identified a new DLX3 variant in one family, recruited as part of an ongoing study of genetic variants associated with AI. Targeted clinical exome sequencing of two further families revealed another new variant of DLX3 and complete heterozygous deletion of DLX3 . For all three families, the phenotypes were shown to consist of AI and taurodontism, together with other attenuated features of TDO. Results: c.574delG p.(E192Rfs*66), c.476G>T (p.R159L) and a heterozygous deletion of the entire DLX3 coding region were identified in our families. Conclusion: These previously unreported variants add to the growing literature surrounding AI, allowing for more accurate genetic testing and better understanding of the associated clinical consequences.